THEORY OF SENTENCE AND PARTS - Teshaboyeva Nafisa Zubaydulla qizi; Egamberdiyeva Oyguljon (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation:This  article  delves  into  the  theory  behind  sentence  components, analyzing the primary, secondary, and tertiary elements that create sentence structures in  English.  The  foundational  elements,  such  as  subjects,  predicates,  objects,  and complements,  are  essential  for  constructing  sentences.  Principles  like  agreement, consistency, and parallelism play a crucial role in maintaining clarity and correctness. Secondary elements, including modifiers, phrases, and clauses, enhance meaning and add detail. Additionally, the article discusses tertiary components, like conjunctions, interjections, and transitional devices, while pointing out the difficulties they can pose in ensuring sentence coherence. By grasping these elements, individuals can improve their skills in crafting effective and grammatically accurate sentences.